2012
DOI: 10.7150/ijbs.5106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metastamirs as Metastasis-associated MicroRNAs in Clear Cell Renal Cell Carcinomas

Abstract: MicroRNAs (miRNAs) play a pivotal role in cancerogenesis and cancer progression, but their specific role in the metastasis of clear cell renal cell carcinomas (ccRCC) is still limited. Based on microRNA microarray analyses from normal and cancerous samples of ccRCC specimens and from bone metastases of ccRCC patients, we identified a set of 57 differentially expressed microRNAs between these three sample groups of ccRCC. A selected panel of 33 miRNAs was subsequently validated by RT-qPCR on total 57 samples. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 44 publications
11
64
0
1
Order By: Relevance
“…Consistent with the statistical result of Wotschofsky et al from GSE37989 in GEO database (24) (Fig. 1A), real-time PCR indicated that miR-204 expression was markedly downregulated in 90% (59/65) of the RCC tissues (P<0.0001; Fig.…”
Section: Mir-204 Is Downregulated In Rcc Tissues and Cell Linessupporting
confidence: 76%
“…Consistent with the statistical result of Wotschofsky et al from GSE37989 in GEO database (24) (Fig. 1A), real-time PCR indicated that miR-204 expression was markedly downregulated in 90% (59/65) of the RCC tissues (P<0.0001; Fig.…”
Section: Mir-204 Is Downregulated In Rcc Tissues and Cell Linessupporting
confidence: 76%
“…In Caki-1 cells of the present study, miR-143 was undetectable and consequently it could not be evaluated in relation to drug treatment. Though, it is worthwhile mentioning that the expression status of miR-143 in Caki-1 cells has been also reported in renal tissues surgically removed from patients with metastatic RCC [40]. Contrary to miR-143, the expression of miR-145 was evaluated in Caki-1 cells treated with sunitinib or everolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR20a, miR-106b, miR-141, and miR-205 were found to be upregulated in bladder cancer, 17,18 in contrast to an inverse expression behavior in other locations such as renal or prostate cancer. 18,19 miRNA profiling studies in bladder cancer patient stratification…”
Section: -9mentioning
confidence: 99%